US consumers’ mental associations with meat substitute products - Garaus, Marion; Garaus, Christian (Frontiers in Nutrition, 2023)
Negative impacts of meat consumption on both consumers’ health and the environment call for alternative sources for protein intake. In the last decades, the development of meat substitute products has made enormous progress. Given the beneficial aspects of reduced meat consumption, meat substitutes might be a promising approach for a more plant-based diet. However, despite the continuous improvement of meat substitute products and their increasing market potential, meat consumption in the US is still at a high level. Extant literature acknowledges that meat substitute products prompt several negative thoughts and feelings in various European countries, while US consumers’ perceptions of meat substitute products have not been investigated so far. However, understanding consumers’ thoughts and feelings toward meat substitute products provides valuable insights which can help policymakers and marketers to efficiently promote meat substitute products. Against this background, the current research investigates US consumers’ mental associations (i.e., connections of information and prior experiences with the product category stored in memory) with meat substitute products and explores if there are any differences between women and men. A sample of 175 US citizens acquired through an online panel provider completed a free word association technique resulting in 824 mental associations that qualified for the subsequent analysis. In a deductive-inductive content analysis, we assigned the mental associations to 20 categories (e.g., taste, health, environment) and determined their valence (i.e., positive, neutral, or negative). Frequencies and relationships among the categories were analyzed by employing frequency analyses, Chi-square difference tests, and multidimensional correspondence analysis. The findings reveal that meat substitute products elicit more negative mental associations than positive ones. Results validate categories identified in existing literature, but also reveal new categories of mental associations. Furthermore, the findings demonstrate that mental associations differ between women and men, with women tending to perceive meat substitutes more negatively than men. The multiple correspondence analysis resulted in four different consumer profiles (skeptics, innovators, health-oriented consumers, and avoiders) which can guide policymakers and brand managers on the effective promotion of meat substitute products.